The Effect of Fraction Blocks Media on Elementary School Students’ Mathematics Learning Outcomes in Fraction Topics: A Literature Review - Sari, Ida Purnama; Mardiyana, Mardiyana; Supianto, Supianto; Gunarhadi, Gunarhadi (Social, Humanities, and Educational Studies (SHES): Conference Series, 2026)
Fraction instruction in elementary schools still faces several challenges because of its abstract character and the limited use of concrete media, which ultimately leads to subpar student’ learning outcomes. This study aims to synthesize the effect of using fraction blocks on elementary students’ mathematics learning outcomes in fraction topics. This study employed a systematic literature review approach based on PRISMA guidelines. The literature search was conducted within the 2015–2025 period through Google Scholar, Garuda, and DOAJ databases using relevant keywords related to fraction blocks, concrete fraction media, mathematics learning outcomes, and elementary students. The inclusion criteria covered studies on fraction learning using concrete media at the elementary level and reporting learning outcomes, while the exclusion criteria included irrelevant articles and those without full-text access. From an initial 38 articles, 32 remained after duplicate removal, 14 were screened, and six articles were analyzed. The results of the review indicate that the use of fraction blocks media consistently has a positive impact on students’ mathematics learning outcomes, particularly in improving conceptual understanding of fractions, learning mastery, and student engagement in the learning process. Fraction blocks media help students connect abstract fraction concepts with concrete representations, thereby facilitating thinking processes and problem-solving skills. Overall, this study confirms that fraction blocks are an effective alternative instructional medium for improving mathematics learning outcomes in fraction topics at the elementary school level. These findings have practical significance for teachers in designing more contextual mathematics learning that aligns with the cognitive developmental characteristics of elementary school students.